An Overview of The Incidence of Acne Due to The Use of Masks During The COVID-19 Pandemic - Febriyanti, Monica Syefi; Sitanggang, Christanti Naomi Pramasanti; Zebua, Ribka Liliana; Widiyani, Syahfori (Talenta Publisher, 2024)
Background: On March 11 2020, WHO declared COVID-19 as a pandemic. One of the efforts to prevent, control and break the chain of transmission of COVID-19 in the community is to use a mask. However, apart from feeling uncomfortable, many complaints about acne due to the use of masks are found in the community. During the COVID-19 pandemic, a popular phenomenon appeared on social media, namely